Occupancy based architecture A case of traditional Savunese House in East Nusa Tenggara Province - Desak Putu Damayanti; I Ketut Suwantara; I Gusti Ngurah Antaryama; Ima Defiana (Institut Teknologi Sepuluh Nopember, 2017)
Many studies have concluded that traditional house works in close relationship with climate of a place. The studies also stated that building played an important role in determining the good indoor climatic conditions, but some of the study indicated that aside from the influence of building, occupant also governed the climatic performance. The present study closely investigated traditional Savunese house in East Nusa Tenggara-Indonesia, and was aimed to identify relationship of occupancy pattern with thermal condition of the building. Primary data were obtained from field observation and interview. These included indoor, outdoor air temperature, and occupancy pattern. Data obtained from BMKG (Meteorology, Climatology, and Geophysics Agency), representing average climatic condition of a ten-year period. The measurement of air temperature was done using Memory Hilogger, and observation and structured interviewed sheets were employed to record occupancy pattern. The study showed that during the dry season, the building was only experienced daily comfortable conditions for 14 hours (58%). Out of these 14 hour comfortable conditions, 79% of the time occurred when the inhabitant were in the building. The study concluded that building elements were not the sole determinant of its good performance, but the way inhabitant occupied the house was also the contributor.